2022
DOI: 10.1093/jn/nxac200
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin Attenuates Intestinal Barrier Dysfunction and Inflammation by Modulating the MAPK Pathway and Gut Microbes in Mice

Abstract: Background Deoxynivalenol (DON) is a major mycotoxin present in staple foods (particularly in cereal products), which induces intestinal inflammation and disrupts intestinal integrity. Lactoferrin (LF) is a multifunctional protein that contributes to maintaining intestinal homeostasis and improving host health. However, the protective effects of LF on DON-induced intestinal dysfunction remain unclear. Objectives This study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Previous research revealed that DON induced a hepatic inflammatory response by promoting the production of pro-inflammatory cytokines, such as IL-1β and TNF-α . Congruently, our previous study showed that DON increased the plasma IL-1β level, and the present findings further support this by revealing that DON upregulated the hepatic mRNA levels of IL1β , IL8 , and TNFα in mice. As expected, LF treatment inhibited the expression of IL1β and TNFα in the liver of DON-exposed mice.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Previous research revealed that DON induced a hepatic inflammatory response by promoting the production of pro-inflammatory cytokines, such as IL-1β and TNF-α . Congruently, our previous study showed that DON increased the plasma IL-1β level, and the present findings further support this by revealing that DON upregulated the hepatic mRNA levels of IL1β , IL8 , and TNFα in mice. As expected, LF treatment inhibited the expression of IL1β and TNFα in the liver of DON-exposed mice.…”
Section: Discussionsupporting
confidence: 87%
“…The groups were as follows: the vehicle group (Veh group) received peroral physiological saline daily with a commercial diet; the LF group received peroral 10 mg of LF/day with a commercial diet; the DON group received peroral physiological saline daily with a DON diet (commercial diet containing 12 mg of DON/kg); and the LF + DON group received peroral 10 mg of LF/day with a DON diet. More detailed information regarding the grouping can be found in previous literature . The composition of the diet is shown in Table S1 of the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, LF concomitantly stimulated intestinal epithelium growth and up-regulated the expression of jejunal tight-junction proteins such as zonula occludens and claudins in response to caloric restriction-mediated malnutrition [ 45 ]. The restoration of intestinal integrity, reflected by raised occludin mass and tight junction structure normalization, was caused by the inactivation of the MAPK pathway, in particular via the decrease of p38 and ERK1/2 phosphorylation [ 27 ]. The strengthening of the intestinal barrier was also accompanied by elevated alkaline phosphatase activity and transepithelial electrical resistance, the latter as an indicator of the strength of tight-junction proteins [ 46 ].…”
Section: General Lactoferrin Propertiesmentioning
confidence: 99%
“…(The images used were extracted from Servier Medical Art). Related references cited in the Figure: ( a : [ 11 , 12 , 13 , 14 , 15 , 16 ]; b : [ 16 , 17 ]; c : [ 18 ]; d : [ 11 , 19 ]; e : [ 19 ]; f : [ 20 , 21 ]; g : [ 20 , 22 ]; h : [ 23 ]; i : [ 24 , 25 , 26 ]; j : [ 25 , 27 , 28 , 29 ]; k : [ 30 , 31 ]; l : [ 32 ]; m : [ 33 , 34 ]; n : [ 11 , 19 ]; o : [ 15 ]; p : [ 11 , 15 , 19 ]; q : [ 16 , 35 , 36 ]; r : [ 16 , 37 ]; s : [ 11 , 35 , 38 ]; t : [ 16 , 38 ]; u : [ 16 ]; v : [ 39 ]; ...…”
Section: Figurementioning
confidence: 99%